1982
DOI: 10.1111/j.2044-8341.1982.tb01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Some marital and child‐rearing characteristics of early mother‐bereaved women

Abstract: A sample of 160 female, psychiatric patients from North‐east Scotland whose mothers died before they were aged 11 was compared with 80 non‐bereaved, female, psychiatric patients, matched by decade of birth, from the same area. Six subgroups of the bereaved patients classified according to the events which followed the bereavement were also examined. In addition, samples of 44 and 27 women from the Chichester general population, whose mothers died before age 11 and from 11 to 19 respectively, were paired by age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…These findings add to previous reports of adults who lost parents as children that found difficulties in intimacy, parenting, lower perceived support, and lower educational attainment compared to non-bereaved controls (Birtchnell & Kennard, 1982; Hepworth et al, 1984; Maier & Lachman, 2000; Marks et al, 2007). Studies conducted in Ethiopian and in Indonesian youth who lost their parents to HIV/AIDS or to a tsunami, respectively, also showed the negative impact of parental death on children’s school attendance, educational aspirations, and optimism about the future (Cas et al, 2011; Himaz, 2009).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings add to previous reports of adults who lost parents as children that found difficulties in intimacy, parenting, lower perceived support, and lower educational attainment compared to non-bereaved controls (Birtchnell & Kennard, 1982; Hepworth et al, 1984; Maier & Lachman, 2000; Marks et al, 2007). Studies conducted in Ethiopian and in Indonesian youth who lost their parents to HIV/AIDS or to a tsunami, respectively, also showed the negative impact of parental death on children’s school attendance, educational aspirations, and optimism about the future (Cas et al, 2011; Himaz, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…To date, there is a limited literature linking parent loss to positive, adaptive, developmental outcomes. Early retrospective studies of childhood bereavement, typically in case series or controlled studies in referred or convenience samples, found that adults who lost a parent during childhood were more likely to have difficulties in educational attainment, the establishment of intimate and stable relationships, and parenting their own children (Balk, 1991; Birtchnell & Kennard, 1982; Harris, 1991; Hepworth, Ryder, & Dreyer, 1984; Jacobson & Ryder, 1969; Ragan & McGlashan, 1986). …”
Section: Introductionmentioning
confidence: 99%